Does team work make the dream work? (and other claims of student-oriented mathematics instruction) - Andrew G. Biggs; John Mantus (American Enterprise Institute (AEI), 2024)
There is much public concern over the poor math performances of U.S. students compared to other developed countries. In this paper, we consider the role of instruction style in student performance on the math literacy portion of the OECD's PISA exam, specifically looking at the increasingly-popular student-oriented style of classroom instruction versus the more traditional teacher-directed instruction style. The 2012 PISA exam is unique in including a student questionnaire with questions pertaining to how math is taught in their classroom. We first enhance the robustness of question-level results produced by the OECD in Echazarra et al. (2016), confirming their finding that traditional teacher-directed instruction style is superior to student-oriented instruction, regardless of question difficulty. These results contradict the OECD's conclusion in Weatherby (2016) that the 2012 PISA data justify the employment of both math instructional philosophies. We then study overall exam data at both an international- and student-level and find strong evidence that student-oriented instruction is associated with lower math scores and teacherdirected instruction with higher ones. At the country level, the United States' greater use of student-oriented math instruction accounts for roughly one quarter of the 2012 PISA score difference between the U.S. and Korea, which had the second highest average score in the 2012 exam and the highest use of teacher-directed instruction. At the student level, a one standard deviation increase in the use of student-oriented mathematics instruction correlates with a decline in PISA exams scores of 0.27 standard deviations, while a one standard deviation increase in teacher-directed instruction corresponds with a 0.19 standard deviation increase in math scores. These effects are comparable in size to a one standard deviation increase in a student's socioeconomic status or the student living with both parents rather than a single parent. These results imply that mathematics instructional methods result in differences in mathematics proficiency that are not only statistically significant but meaningful in size. These results contradict the teaching recommendations provided by the OECD and suggest that increased utilization of teacher-directed instructional methods could potentially improve U.S. math performance.
Keywords: 330; education assessment; math; Standardized testing